Designing a security-oriented leadership model of Mazandaran University of Medical Sciences - Saeid Miladigorji; Mohammad Hassan Shakki; Mojtaba Rezaei Rad (مدیریت و چشم انداز آموزش)
Abstract The goal is designing a security-oriented leadership model of Mazandaran University of Medical Sciences, which is a fundamental study in terms of research orientation, and a mixed exploratory one in terms of data analysis method. The statistical population of the research includes professors and knowledgeable experts in the field of human resources management and members of the faculty of Mazandaran University of Medical Sciences. Sampling in this study was available. Based on the topic of data and information through preliminary studies, the semi-structured interviews of collection and sampling continued until reaching the theoretical saturation level, and after conducting 8 interviews and reaching the theoretical saturation level, the interviews were ended. The acquired information was analyzed by MAXQDA2020 software. The results have shown that in the model presented regarding the safety-oriented leadership model of Mazandaran University of Medical Sciences, among the causal factors (components of acceptability and respect for values), the core categories (providing exploration through emphasizing on growth and handling tasks and situations through a positive method), background conditions (employee support), intervention (attention to the organization's policies), strategic factors (influencing subordinates' thoughts) and consequences (creating morale and motivation in employees) has received more attention. Extended abstract Introduction One of the most important elements in any organization is its management, which causes coherence and order in affairs. In order to achieve an efficient organization, the manager is obliged to act according to his professional duties and with proper and appropriate use of the facilities so as to obtain the best and most effective results. In order to achieve this, managers must be familiar with the basics of power and leadership in organizations and methods of influencing subordinates. Security-oriented leadership, used by leaders, is a process to influence the desired success of the vision and is accompanied by influencing the organizational culture, allocation of resources, guidance through policy-making and consensus on a complex, ambiguous, unreliable and transient global environment characterized by opportunities and threats. In the definition of security-oriented leadership, it can be stated that this type of leadership is mostly considered as a safe base that covers the generality of its organization well. This style of leadership can facilitate the possibility of efficient and productive intra-organizational cooperation, because in such organizations, communication flows parallel to trust. It is no secret that most of today's organizations struggle with various issues, including technological developments, resource limitations, energy problems, etc. (Obeydi et al, 2023). Naturally, in such a situation, organizations are looking for frameworks to maintain and improve their competitive advantage and ultimately lead to their continued survival in the global competitive environment. All these factors work hand in hand and will make the organization progress compared to competing organizations. In the meantime, having a productive, committed and effective workforce requires strong leadership in organizations. The organizational environment can influence the behavior of employees and strong management principles can improve the performance of employees and ultimately lead to organizational excellence. One of the responsibilities placed on the shoulders of every management is to create enough motivation among the employees to perform their duties well and as they were told. The topic of leadership and management is one that has attracted the attention of many researchers and management science researchers (Sadeghi, 2021). Considering that universities of medical sciences play an essential role in promoting the health of the society, it is recommended that in order to evaluate the sustainability in the university, careful planning should be done by the managers and practitioners of the higher health education system. In this context, the transformation and innovation package in medical science education has been implemented by the Ministry of Health, Treatment and Medical Education, one of the packages discusses the movement towards leadership systems and the role of management in influencing employees, which oversees three general policies of institutionalization of the management approach in the health system, being present in regional and global educational arenas, and producing and localizing valid scientific evidence for the promotion of higher health education (Obeydi et al, 2023). Since the development of the University of Medical Sciences and the achievement of its educational goals is through the style and type of management and leadership in its employees, it is very important in the direction of competitive advantage in the present era; therefore, in view of the fact that it plays an important role in the health of the society, universities of medical sciences should try to promote all-round development; and from one point of view, there is very little information about the type of security-oriented leadership style in the university, as a style that has more influence on employees, and no research has been done about the presentation of the model in the universities of medical sciences, so with regard to the presented materials, the main question of the present research is: how is the development model of the security-oriented leadership style at Mazandaran University of Medical Sciences? Theoretical literature Security: Security means predicting and providing government assistance to meet people's needs in times such as illness, unemployment, old age, being immune and free from threats or illegal actions (Sadeghi, 2021). Security-oriented leadership: In the definition of security-oriented leadership, it can be stated that this type of leadership is considered more as a safe base that well covers the generality of its organization (Obeydi et al, 2023). Moqar et al, (2023) conducted a research titled "The effect of security-oriented leadership on nurses' ethical behaviors: explaining the moderating role of individual resilience". The research method was descriptive-correlative. The statistical population of the research was made up of nurses of public hospitals in Mazandaran province. Sampling method was available. The results showed that safety-oriented leadership has a positive and significant effect on nurses' ethical behaviors. Also, the moderating role of the individual resilience variable in the relationship between the impact of security-oriented leadership on nurses' ethical behaviors was also confirmed. Hosseini et al, (2021) in a study titled predicting the organizational voice of teachers based on the security-oriented leadership of school principals, showed that there is a positive and significant relationship between the security-oriented leadership style and the organizational voice of teachers. The results of multiple regression analysis indicate that among the components of security-oriented leadership style of school principals, two components of observing the potential and investigating had the ability to predict the organizational voice of teachers. Research methodology The current study is a fundamental study in terms of research orientation, and an exploratory mix in terms of data analysis method. The statistical population of the research includes professors and knowledgeable experts in the field of human resources management and members of the faculty of Mazandaran University of Medical Sciences in the human resources department. The technique used in sampling in this research was non-random snowball sampling. Based on the topic of data and information through preliminary studies, semi-structured interviews were collected and sampled until reaching the theoretical saturation limit, and after conducting 8 interviews and reaching the theoretical saturation limit, the interviews were ended. The opinions of the present experts were analyzed in the form of a qualitative interview, using the theoretical coding approach based on grounded theory methodology (identification of open codes, categories and concepts) and using MAXQDA software. Research findings In the model presented regarding the safety-oriented leadership model of Mazandaran University of Medical Sciences; among the causal factors, the components of acceptability and respect for values according to the point of view of the interviewees have received more attention in this section. Based on the presented model, the central category of components such as providing exploration by emphasizing growth and handling tasks and situations through a positive method have been noticed by the interviewees. Another influential dimension in this model is the context dimension, which according to the opinion of the interviewees in the safety-oriented leadership model of Mazandaran University of Medical Sciences; support for employees, fairness and maintaining peace and deep emotional connection received more attention. From the point of view of the intervenor, the interviewees paid attention to the organization's policies, the culture of trust and creating an atmosphere full of peace in the security-oriented leadership model of Mazandaran University of Medical Sciences. In terms of strategic factors, the interviewees were more focused on influencing subordinates' thoughts, using others' potential, and creating opportunities for subordinates. Regarding the consequences aspect, the interviewees focused on creating morale and motivation in employees and positive organizational development and change, creating creativity and innovation, learning organization and creating job satisfaction; and other components assumed less attention. Discussion and conclusion In the model presented regarding the safety-oriented leadership model of Mazandaran University of Medical Sciences; according to the interviewees, the components of acceptability (the acceptability of leadership in an ambiguous and complex environment) and respect for values ​​(the manager's speech about the organization's basic beliefs and values ​​and leadership of people's thought, speech and behavior) among the causal factors are paid more attention in this section. Based on the presented model, the central category, along with causal factors, has been observed to be effective in the security-oriented leadership model of Mazandaran University of Medical Sciences. Among these factors are components such as providing exploration by emphasizing growth (development and potential and exploring) and handling tasks and situations through a positive method (prioritizing tasks in time management) have been noticed by the interviewees. Another influential dimension in this model is the context dimension, which according to the opinion of the interviewees in the safety-oriented leadership model of Mazandaran University of Medical Sciences; support for employees (high standards of ethical behavior with employees), fairness and maintaining peace ( having harmony, emotional health) and deep emotional connection (emotional and mental relationships in the work environment) have been more important. From the perspective of the interventionist, the interviewees paid attention to the organization's policies (challenges of power sharing and conscious measures of influence), the culture of trust (enhancement of participation) and the creation of an atmosphere full of peace (preventing feelings of inferiority) in the security-oriented leadership model of Mazandaran University of Medicine Sciences. In terms of strategic factors, the interviewees are more focused on exerting influence on the thoughts of subordinates (managers' independence), using the potential of others (growing and developing the talents of employees) and creating opportunities for subordinates (providing solutions for the organization's problems with the motive of profiting them and carefully planning). In terms of the results aspect, the interviewees were interested in creating morale and motivation in employees (increasing employee self-confidence), positive organizational development and change (developing and expanding employees' abilities), creating creativity and innovation (creating innovative ideas), the learning organization (the importance of having a sense of group cooperation about the mission) and creating job satisfaction (satisfaction with salaries and benefits and satisfaction with the supervisor) has been focused, and less attention has been paid to other assumed components.